Cohabitation By Parties Who Are Still Bound By Marriage And Its Qualification As An Unlawful Act - Putri Sindi Rinata; Gusti Yosi Andri (Jurnal Legisci, 2026)
Background. The practical implications of cohabitation remain a primary topic within the realms of moral and criminal law; however, studies addressing cohabitation in terms of civil liability for parties still bound by marriage are limited. Aims. This research aims to discuss cohabitation among married individuals based on the perspective of Law Number 1 of 1974 concerning Marriage and to determine its qualification as an unlawful act (PMH) referring to Article 1365 of the Civil Code. Methods. The study employs a normative legal method, using legislation and conceptual analysis. Result. The findings demonstrate that cohabitation contradicts the duty of fidelity in marriage and lacks legal legitimacy since it occurs without a valid bond, spousal consent, or court approval. Conclusion. Furthermore, cohabitation meets the criteria of an unlawful act, including an act, unlawfulness, fault, material and immaterial losses, and a causal relationship, thereby enabling the involved parties to be held civilly liable for damages.